A prospective cohort study of Staphylococcus aureus and methicillin-resistant Staphylococcus aureus carriage in neonates: the role of maternal carriage and phenotypic and molecular characteristics - Lin J; Wu C; Yan C; Ou Q; Lin D; Zhou J; Ye X; Yao Z (Infection and Drug Resistance, 2018)
Jialing Lin,1 Chuanan Wu,2 Chunrong Yan,2 Qianting Ou,1 Dongxin Lin,1 Junli Zhou,1 Xiaohua Ye,1 Zhenjiang Yao1 1Department of Epidemiology and Health Statistics, School of Public Health, Guangdong Pharmaceutical University, Guangzhou, China; 2Maternal and Child Health Care Center of Longhua District, Shenzhen, China Background: Staphylococcus aureus, particularly methicillin-resistant S. aureus (MRSA), in mothers can cause serious outcomes in neonates. We aimed to elucidate the associations of S. aureus and MRSA carriage between mothers and neonates. Methods: A prospective cohort study was conducted between August and November 2015 in two hospitals in Shenzhen, China. Chinese pregnant women and their neonates who met the inclusion criteria were included in this study; samples and relevant information were collected. We assessed maternal–neonatal associations by using Poisson regression models. Results: Overall, 1834 mothers and their neonates were included in this study. The prevalence of isolate carriage among the mothers was as follows: S. aureus (nasal, 25.8%; vaginal, 7.3%; and nasal and vaginal, 3.3%) and MRSA (nasal, 5.7%; vaginal, 1.7%; and nasal and vaginal, 0.5%). The incidences of S. aureus and MRSA carriage among neonates were 3.3% and 0.8%, respectively. Of the 21 maternal–neonatal pairs with S. aureus carriage, 14 were concordant pairs with the same phenotypic and molecular characteristics. After adjustment, the relative risks and 95% confidence intervals (CIs) between the S. aureus carriage of neonates and nasal S. aureus carriage, vaginal S. aureus carriage, and both nasal and vaginal S. aureus carriage of mothers were 2.8 (95% CI, 1.6–4.8), 7.1 (95% CI, 4.1–12.4), and 9.6 (95% CI, 4.2–22.4), respectively. Conclusion: S. aureus carriage in mothers increases the risk for neonates. Keywords: Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, neonates, mothers, maternal–neonatal association